NK4 Regulates Laryngeal Squamous Cell Carcinoma Cell Properties and Inhibits Tumorigenicity by Modulating the DKK1/Wnt/β-Catenin Axis - Zhang, Shoukai; Wei, Hulai; Ha, Xiaoqin; Zhang, Yueyu; Guo, Yufen (Frontiers in Oncology, 2021)
Objective To investigate the effects of NK4 gene on the properties and tumorigenicity in laryngeal squamous cell carcinoma cell. Methods Here, we used the attenuated Salmonella carrying the NK4 gene to transfect the AMC-HN-8 cells and detected the expression of NK4 by the real-time quantitative polymerase chain reaction (q RT-PCR). The properties of NK4 gene was determined by MTT method, cell scratch test, and flow cytometry. A nude mouse tumorigenesis model was used to evaluate the effect of NK4 gene on the growth of AMC-HN-8 cells in vivo. While a western blot assay was used to assess the expression of DKK1, Wnt1 and β-Catenin in nude mouse tumors. Results qRT-PCR showed that the expression of NK4 in the transfection group was significantly higher than that in the control group (P<0.01), and the expression increased with the time of transfection. MTT results showed NK4 overexpression inhibited the proliferation of AMC-HN-8 cells, and the inhibitory activity no longer increased with increasing dose when 30% expression supernatant was added (P<0.01). Scratch experiment showed that NK4 overexpression decreased the cell migration ability (P<0.01). Annexin V/PI double staining experiment showed that NK4 gene induced AMC-HN-8 cell apoptosis (P<0.01), and cell cycle arrest in S phase (P<0.01). NK4 overexpression inhibited tumor formation ability of AMC-HN-8 cells in vivo (P <0.05). WB detection showed that the expression of DKK1 increased, Wnt1 and β-Catenin protein decreased after the high expression of NK4. Conclusions NK4 gene inhibit cell proliferation and migration, while promote cell apoptosis, and induce cell cycle arrest in S phase of laryngeal carcinoma AMC-HN-8 cells. NK4 overexpression inhibit the tumorigenesis ability of AMC-HN-8 cells, which may be related to the regulation of DKK1/Wnt1/β-Catenin signal axis.